Microcatheter-Assisted Trabeculotomy Combined With Deep Sclerectomy and Trabeculectomy in Young to Middle-Aged Adults With Advanced Primary Open-Angle Glaucoma: 1-Year Result - Zhang, Hengli; Yan, Xiaowei; Li, Fan; Ma, Lihua; Geng, Yulei; Jiao, Kexin; Tang, Guangxian (Frontiers in Medicine, 2021)
Objective: To evaluate the safety and clinical efficacy of microcatheter-assisted trabeculotomy combined with deep sclerectomy and trabeculectomy (MATT-DS-Trab) in the surgical management of advanced primary open angle glaucoma (POAG). Methods: According to the inclusion criteria, we retrospectively collected and analyzed 37 POAG cases in advanced stage who received MATT-DS-Trab. The intraocular pressure (IOP), best corrected visual acuity (BCVA), use of anti-glaucoma drugs, shape of filtering bleb, size of scleral lake, complications and the surgical success rate were recorded. Results: The mean IOP was 37.50 ± 8.11 mmHg before the operation, while it decreased to 10.08 ± 2.01 mmHg and 11.43 ± 2.07 mmHg at 1 week and 12 months after operation respectively (both P values＜0.001 compared to pre-operative IOP). Only 0-2 kinds of anti-glaucoma drugs were used 12 months after surgery in the patients, which were significantly reduced compared with preoperatively (P < 0.001). L-type filtering bleb was the main form at all time points after operation. Following the surgery 12 months, F-type filtering bleb accounted for 5.41% and no E-type filtering bleb were recorded. The length and height of scleral lake decreased with time, but there was no statistical significance (P > 0.05). Also, there was no correlation between scleral pool size and intraocular pressure (P > 0.05). At 12 months after operation, the complete success rates were 94.59%, 83.78% and 72.97% according to standard A (≤18mmHg), B (≤15mmHg) and C (≤12mmHg) respectively. Intraoperative complications were mainly anterior chamber hemorrhage, and no complications related to filtrating bleb were found after the operation. Conclusion: Based on multi-channel mechanisms, MATT-DS-Trab is able to effectively reduce IOP in advanced POAG patients, with few serious complications and high success rate.